ISOLATION OF Pichia manshurica PROTOPLAST FROM Dahlia sp. PLANT - Wijanarka Wijanarka; Endang Sutariningsih Soetarto; Kumala Dewi; Ari Indrianto (The East Java Biological Society, 2013)
Isolation of protoplasts is an important step in the fusion process. Protoplasts are cells that have eliminated the cell wall, but the cell membranes and organs can still function properly. Pichia manshurica is one of indogenous yeast that derived from Dahlia’s plants. The success rate protoplast isolation was determined by various factors, include the age of the culture and the used of lytic enzymes. The purpose of this research is to get the perfect age of yeast culture that is ready to be harvested and also to get the appropriate concentration of Glucanex lytic enzymes which used for protoplast isolation. The yeast of Pichia manshurica grown on YPD broth medium and growth observed in turbidimetry. Observation of the growth of yeasts performed every 6 hours for 42 hours. Glucanex lytic enzyme concentration used for the isolation of protoplasts is 0 mg / mL (L0 = control), 2 mg / mL (L2) and 4 mg / mL (L4). The results showed that the age of the culture is right and ready for harvest at the age of 24 hours and Glucanex lytic enzyme concentration of 4 mg / mL (L4) is able to produce the best of protoplasts at 7.2 x 1010.